Two new species of freshwater crabs of the genus Heterochelamon Türkay & Dai, 1997 (Crustacea: Decapoda: Brachyura: Potamidae) from Guangxi Zhuang Autonomous Region, southern China - Naruse, Tohru; Zhu, Chunchao; Zhou, Xianmin (Zootaxa, 2013)
Heterochelamon tessellatum n. sp. and H. castanea n. sp. are described from the Guangxi Zhuang Autonomous Region, southern China. Heterochelamon tessellatum n. sp. and H. castanea n. sp. are morphologically most similar to H. yangshuoense Türkay & Dai, 1997, and H. guangxiense Türkay & Dai, 1997, respectively. The new species can be differentiated from these allied species by differences in the shape of external orbital tooth, epibranchial tooth, and male first gonopod. The present study brings the number of Heterochelamon species to five. A key to species of the genus Heterochelamon is provided.